Years Lived with Disability due to Alzheimer's Disease and Other Dementias in Asian and North African Countries: A Trend Analysis - Maedeh Amini; Farid Zayeri; Sahar Saeedi Moghaddam (Springer, 2019)
In Asia, which has a rapidly aging population, dementia is the most prominent disease. This article presents an application of Latent Growth Mixture Model (LGMM) to identify classes of individual Alzheimer's Disease (AD) and other dementias Years Lived with Disability (YLD) rates for Asian and North African countries based on the unobserved heterogeneity. The AD and other dementias YLD data for both sexes and age-standardized groups reported by the Global Burden of Disease (GBD) Study database during 1990-2015 for 55 Asian and North African countries were analyzed via LGMM. Findings of LGMMs identified four classes of YLD trajectories. Among the specified classes, a class was related to a single country (Turkey) with the highest starting point in 1990 (intercept of 218.52 per 100,000) and upward trend. Another class with increasing trend (a slope of 2.66 per 100,000) consisted of India, China, Singapore, Japan, and Egypt. Other countries in Asia and North Africa (Classes 3 and 4) had a downward trend of YLD rates. The upward trend for some parts of Asia and North Africa might be attributed to appropriate therapeutic strategies, higher levels of awareness, related medical cares, and increase in life expectancy in these countries.